A CASE OF BONE CHORDOMA (CANCER) IN A CHANCAY INDIVIDUAL OF CERRO COLORADO, SANTA MARIA-HUAURA - van Dalen Luna, Pieter (2015)
This article presents the diagnosis of a case of bone cancer in a human individual from the Chancay culture recovered in the funeral area of Cerro Colorado, southern end of the valley of Huaura. Cerro Colorado is a vast archaeological complex consisting of several sectors among which: the Tambo Tawantinsuyu, the walled sector and extensive funerary area, occupied now many human settlements and housing associations.